Substantiation of production technology of tablets “AP-helmin” - Semchenko, Kateryna; Vyshnevska, Liliia; Gladukh, Ievgenii; Sichkar, Antonina (ScienceRise: Pharmaceutical Science, 2020)
The aim. The purpose of this work is to substantiate the technology of “AP-helmin” tablets preparation and to establish the possible critical parameters of the production process. Materials and methods. Objects such as a mixture of pure substances albendazole and praziquantel in the ratio (1:4), tablet mass and tablet core samples were used in the research. The usual physicochemical and pharmacotechnological methods of the State Pharmacopoeia of Ukraine were used in the work, namely, the appearance, physical parameters, bulk density, compressibility, flowability, crushing force, determination of average mass, uniformity of mass, resistance to crushing and disintegration time were evaluated. Results. It was found that the mixture of active substances has poor flowability, indicating the need to enter the stage of wet granulation in the development of tablet technology with them. The wet granulation stage was carried out with the addition of such excipients as corn starch, microcrystalline cellulose 101 (MCC-101) and povidone (as a 10 % solution). Studies of the 4 samples of tablet mass allowed establishing the most rational composition for the formation of tablets-cores – sample number 4. The samples of composition No. 4 are white core tablets, homogeneous, without chips and cracks, and with respect to resistance to crushing and disintegration time meet the requirements of SPhU (96 N and 8 min 27 sec, respectively). The next stage of the study was the development of a common technology for the preparation of the tablets “AP-helmin”. In order to ensure proper consumer characteristics, the Opadry II ®YS-1-7027 White ("Colorcon") white coating was introduced. Conclusions. On the basis of the obtained results, a technological scheme of production was prepared taking into account the critical parameters and the forecasted control methods at different stages